EVALUASI SISTEM KOMPENSASI PADA RESTORAN X - Khumairoh, Alvi; Faiza, Nadila; Ghonia, Nurmaisya Al; Zamaya, Raihani Mufti; Kartika, Lindawati (PT Naureen Digital Education, 2024)
Restaurant X is a small and medium enterprises (SME) engaged in the food and beverage sector by offering a variety of Indonesian food menu. SMEs have three main roles, namely as a means to improve the welfare of employees and the community, leveling the economic level of smallholders, and providing foreign exchange to the state. SME efforts as a means to improve the welfare of employees is through the evaluation of compensation. By providing better compensation, employees will be motivated to create a positive and productive work environment. Compensation evaluation is done by identifying the initial salary structure in SME, then analyzed to improve compensation using overlapping, adhered and factor points methods. The analysis showed that the most optimal method is overlapping, with a total salary of Rp137, 224, 291 from the previous Rp129, 850, 000. By using the overlapping method, SME experienced a salary increase of 5.68% or Rp7,374,297.